A mixed-method investigation of the root causes of construction project delays in Afghanistan - Mohammad Basheer Ahmadzai; Kunhui Ye (Heliyon)
Construction projects in Afghanistan are plagued by significant delays, hindering development efforts and incurring substantial economic losses. Currently, a staggering 79 % of projects experience delays, contributing to a critical infrastructure gap in the nation. This research delves into the root causes of these delays, examining their impact on project outcomes and identifying potential mitigation strategies. By considering the perspectives of five key stakeholder groups—clients, consultants, contractors, project managers, and lecturers—the study aims to develop a comprehensive understanding of the causes contributing to delays. A comparative analysis with other conflict-affected countries, such as Ukraine, Pakistan, Palestine, and Iraq, reveals both shared and unique challenges that hinder construction projects in these regions. The research findings highlight the significant impact of security challenges, corruption, and logistical hurdles on construction project delays in Afghanistan. Tailored strategies are essential to address these multifaceted issues and improve project outcomes. This study offers valuable insights for policymakers, practitioners, and researchers seeking to bolster the performance of Afghanistan's construction sector. A key contribution of this research is its novel focus on security-related causes of construction project delays. By explicitly examining and ranking these causes, the study advances our understanding of how security challenges influence project timelines, a previously underexplored area. Additionally, the comparison with other conflict-affected regions lays the groundwork for broader comparisons and the identification of global best practices. Construction project delays in Afghanistan are influenced by a complex interplay of causes, including security challenges, corruption, and logistical hurdles. Tailored strategies are essential to address these multifaceted issues and improve project outcomes. This research provides valuable insights for policymakers, practitioners, and researchers seeking to bolster the performance of Afghanistan's construction sector.